Orientation of Islamic Religious Education in the Era of Globalization and Social Change - Hilma Suryani; Rulitawati Rulitawati; Yahya Yahya (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
The purpose of this study is to reveal how the orientation of Islamic education is in the midst of globalization and social change, because one way is to reveal that the current of globalization demands fundamental changes for every individual. , in looking at the flow of globalization demands a necessity not as a threat. To answer the challenges of globalization, it is necessary to have human resources who are reliable and highly competitive. To realize this, all the roles of Islamic education must present themselves as part of the challenges of globalization. Islamic education is challenged to be able to educate and produce graduates who are highly competitive (qualified). To answer all of this, an appropriate management model for Islamic religious education is needed. Characteristics management morgue-based can answer these challenges.